Hyposalivation and dietary nutrient intake among community‐based older Japanese. Issue 4 (8th May 2015) - Iwasaki, Masanori; Yoshihara, Akihiro; Ito, Kayoko; Sato, Misuzu; Minagawa, Kumiko; Muramatsu, Kanako; Watanabe, Reiko; Manz, Michael C.; Ansai, Toshihiro; Miyazaki, Hideo
Abstract : Aim: Saliva is important for maintaining oral function and regulating oral health. Reduced saliva flow rate, which is common among older adults, has been reported to be associated with perceived chewing and swallowing difficulties; however, its relationship to actual nutrient intake is unclear. The aim of the present cross‐sectional study was to evaluate the relationship between hyposalivation and nutrient intake among older Japanese adults. Methods: The participants were 352 community‐based Japanese aged 80 years. A stimulated salivary flow rate <0.5 mL/min was defined as hyposalivation. Multivariable analysis of differences in nutrient and food intake outcome variables, which were collected through a validated food frequency questionnaire, between groups with/without hyposalivation was carried out using general linear models. Models included adjustment for number of teeth, denture use, sex, income, education, body mass index, smoking status, alcohol use, diabetes, medication, activities of daily living, depression and total calorie intake. Results: The hyposalivation group had significantly lower intake of n‐3 polyunsaturated fatty acid, potassium, vitamin D, vitamin E, vitamin B6 and folate than the group without hyposalivation ( P  < 0.05) after adjusting for confounders. Vegetable, fish and shellfish consumption was significantly lower in the hyposalivation group ( P  < 0.05). Conclusions: Dietary intake was poorer in those with hyposalivation than among those without. A decrease in stimulated salivary flow rate could have negative effects on geriatric nutrition.Geriatr Gerontol Int 2016; 16: 500‐507.